Parenting Education sebagai Model Pendidikan Karakter Anak Usia Dini Berbasis Keluarga - Rohinah, Rohinah (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2016)
Character education is an effort that should involve all parties, both the household and the family, the school and the school environment, and the wider community. A child will grow and develop optimally when the basic needs of the children's rights are met. But in reality often violent behavior and discrimination that actually carried out by her own parents. Violent behavior and racial discrimination by parents of children often occurs due to the psychological impact of the workload and the demands of a career outside the home or it could be due to a lack of knowledge about how to educate and assist children in the home. Hence, early childhood institutions "KB Ceria" is located in a residential Pendowo Asri, Village Pendowoharjo, Sewon, Bantul has the attention and concern for the development of character-based early childhood family. This is evidenced by the role that institutions not only provide education for young protege, but also provide education and insight about assistance to parents (parenting education) and then this organization called the Group Meeting with Parents (KPO).